Tinjauan Yuridis terhadap Kejahatan Perdagangan Organ Tubuh Manusia: Perspektif Hukum Pidana Nasional dan Hukum Pidana Internasional - Suhandi Suhandi; Andri Sutrisno (Decisio: Jurnal Ilmiah Hukum, 2026)
This research aims to examine how national and international criminal laws regulate the crime of human organ trafficking, as well as assess the effectiveness of the application of these laws in the context of crime prevention and eradication. This research uses a normative juridical approach, with library research as a technique for collecting legal materials and analyzed descriptively-qualitatively, namely by describing and interpreting the contents of legal materials that have been collected and then arranged systematically. From this research the author produces the following conclusions: First, that the legal regulation on human organ trafficking in Indonesia is still partial, scattered in various laws and has not focused on the specific aspects of this crime. National criminal law needs to respond to this crime comprehensively. The international level has provided important instruments such as the Palermo Protocol and the Council of Europe Convention, but their implementation at the national level is still limited. Harmonization between national and international law needs to be improved. Secondly, the effectiveness of law implementation in preventing and eradicating the crime of human organ trafficking is still low, characterized by weak law enforcement, lack of protection for victims, and obstacles to cross-border cooperation.